K-bi-Lipschitz equivalence of real function-germs - Birbrair, L.; Costa, J. C. F.; Fernandes, A.; Ruas, M. A. S. (Amer Mathematical Soc, 2007)
In this paper we prove that the set of equivalence classes of germs of real polynomials of degree less than or equal to k, with respect to K-bi-Lipschitz equivalence, is finite.